Recent Molecular Epidemiology of Echovirus 11 Throughout North and West Africa Resulted in the First Identification of a Recombinant Strain from an Acute Flaccid Paralysis Case in West Africa - Ndack Ndiaye; Fatou Diène Thiaw; Adamou Lagare; Thérèse Sinare; Mohamed Lemine Diakité; Serigne Fallou Mbacké Ngom; Ousmane Kébé; Issifi Kollo Abdoulkader; Gassim Cissé; Mohamed Dia; Hermann Nodji Djimadoum; Christelle Ouedraogo Neya; et al. (Viruses)
Echovirus 11 has emerged as a major public health concern, causing sepsis in neonates in many European countries in recent years. In Africa, especially West Africa, where resources and diagnostic capacities are limited, only sporadic cases have been reported. To better understand the recent molecular epidemiology of E11 in West Africa, we characterized twenty-three echovirus 11 strains isolated through the acute flaccid paralysis and environmental surveillance systems for polio from 2013 to 2023, using high-throughput sequencing. Our data are noteworthy due to identifying for the first time a recombinant strain from an acute flaccid paralysis case and represent the first focus to date on molecular characterization of echovirus 11 in West Africa. Moreover, our data show that echovirus 11 diverged from 1970 (95% HPD range, 1961–1979) and evolved into four distinct clades, with the virus spread from West Africa to Europe, exhibiting two introductions in France around 2017, from Senegal and Guinea. Furthermore, the in silico analysis reveals four non-conservative amino acid substitutions in the VP1 sequences of the European strains associated with neonatal sepsis in newborns and a conserved amino acid motif in the VP1 protein toward enterovirus genotypes. Our data provide new insights into the epidemiology of echovirus 11 and point to the crucial need to implement specific surveillance programs targeting non-polio enteroviruses for the rapid identification of emerging or re-emerging enterovirus species, particularly in Africa.